The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jnnfm.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a bubble rising in shear-thinning fluids

Abstract: a b s t r a c tThe motion of a single bubble rising freely in quiescent non-Newtonian viscous fluids was investigated experimentally and computationally. The non-Newtonian effects in the flow of viscous inelastic fluids are modeled by the Carreau rheological model. An improved level set approach for computing the incompressible two-phase flow with deformable free interface is used. The control volume formulation with the SIMPLEC algorithm incorporated is used to solve the governing equations on a staggered Eul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…The results shown in Fig. 19 are similar to the ones obtained by [53] for similar Re numbers (Re ∼ 10). The maximum viscosity values agree well with the values given by the rheological data fitted with the Carreau model.…”
Section: Two-bubble Interaction: Varying the Angle Of Approachsupporting
confidence: 84%
See 1 more Smart Citation
“…The results shown in Fig. 19 are similar to the ones obtained by [53] for similar Re numbers (Re ∼ 10). The maximum viscosity values agree well with the values given by the rheological data fitted with the Carreau model.…”
Section: Two-bubble Interaction: Varying the Angle Of Approachsupporting
confidence: 84%
“…Zhang et al [53] made a similar comparison of their numerical terminal bubble velocities obtained with thinning and Newtonian fluids. In order to make the comparison they changed the value of the flow index (similar to what was done here) but considering a constant zero-shear viscosity value (we considered a shear-rate dependent viscosity).…”
Section: Single Bubble Results and Benchmark Simulationsmentioning
confidence: 83%
“…Therefore, information on the local viscosity distribution around rising bubbles is necessary for the better understanding of the bubble moving behavior in non-Newtonian fluids. Unfortunately, although Zhang et al (2010) numerically explored the local viscosity distribution around bubbles in shear-thinning non-Newtonian fluids using the level set approach, so far there is little experimental information about the local viscosity distribution around bubbles rising in non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al 28 focused on the interaction between two parallel rising bubbles by analyzing the velocity field around bubbles using PIV. Zhang et al 29 applied an improved level set method to simulate the motion of deformable bubble in shear-thinning fluids, and found that two separated zones in the vortex-shedding regime formed as a region of wake with high viscosity appeared. Li et al 30 explored experimentally a hollow cylindrical low viscosity region around the bubble wake and a high viscosity region in the central bubble wake around a rising bubble in CMC fluids.…”
Section: Introductionmentioning
confidence: 99%